Audit Interpretation of Presidential and Vice-Presidential Campaign Finance Reports - Arsyad, Muhammad; Natsir, Sukriah; Dinhi, Zoel Dirga (Universitas Ahmad Dahlan, 2025)
This study critically examines the implementation and interpretation of campaign finance audits in Indonesia’s 2024 presidential and vice-presidential elections. The evaluation is grounded in KPU Regulation No. 18 of 2023 and Assurance Engagement Standard SPA 3000 (Revised 2022) to assess compliance, ensure audit rigor, and enhance public assurance outcomes. Employing a descriptive qualitative approach, the study integrates document analysis, normative review, and comparative evaluation, drawing on audit reports, civil society findings, and international benchmarks. The findings reveal that although all candidate pairs received “Compliant Opinions,” significant deficiencies persist in audit planning, materiality assessment, and evidence collection. Public accounting firms demonstrated limited professional skepticism regarding unreported digital advertising expenditures. These gaps undermine the credibility and transparency expected of campaign audits and diminish their assurance value. Applying credibility theory, this study finds that current audit practices comply with formal regulations but fail to provide substantive public assurance. Limited public access to audit reports weakens democratic accountability, while comparative insights from U.S. practices highlight the need for digital verification, extended timelines, and full disclosure. The study contributes theoretically by extending credibility theory to political finance auditing and practically by offering policy recommendations to strengthen electoral audit credibility in emerging democracies.